Transforming yam seed systems in west Africa - Maroya, N.; Balogun, M.; Aighewi, B.; Mignouna, Djana B.; Kumar, P. Lava; Asiedu, R. (Springer, 2022)
The availability of clean planting materials and functional seed regulatory systems is indispensable for fostering a sustainable seed yam system. The Yam Improvement for Income and Food Security in West Africa (YIIFSWA) project of the International Institute of Tropical Agriculture (IITA) developed the capacity of National Agricultural Research Institutes (NARIs) in their use of standardized Temporary Immersion Bioreactor (TIB) and Vivipak (VP) systems for high-ratio propagation and post-flask handling of yam breeder seed plantlets. Foundation seed was enhanced by supporting five private seed companies in Nigeria and three in Ghana. They were equipped with aeroponic and hydroponic technologies for foundation seed tuber production using single-node vine seedlings. For certified seed, seed yam out-growers were trained in good agronomic practices and entrepreneurship for certified seed tuber production using the adaptive yam minisett technique (AYMT). New certification standards were established for various classes of seed produced using different propagation methods and quality assurance procedures in Ghana and Nigeria. The capacity of the national regulatory organizations in both countries was enhanced to implement seed quality control and certification. Increased public sensitization and advocacy were done to raise awareness among relevant stakeholders to enhance the uptake of the seed propagation technologies and ensure a smooth interaction between the public and private sectors. This chapter summarizes the accomplishments of YIIFSWA in Ghana and Nigeria and the spillover impact on the yam belt of West Africa and beyond. The key lessons could inform the design and implementation of more effective seed projects, especially for vegetatively propagated crops.